A prática profissional na graduação de medicina sob a perspectiva do luto - Silva, Tainá Souza e (2023)
The following work addresses, in the form of a reflective narrative, the trajectory of a medical student at the Federal University of São Carlos (UFSCar) over the six years of college, focusing on professional practice and other educational instruments that supported the construction of medical practice throughout training. Throughout the course, students are exposed to the grief of Family members, patients and face their own processes of working through the loss. The text explores the subject from the perspective of grief and its many college presentations.